"Congrats, you are the new COO - now implement a re-organization" : planning for change at a nonprofit - Berka, Gregory Charles; Schneider, Beth Z.; Fine, Allison S. (London : Society for Case Research, 2023)
Amy Stowe, the newly appointed Chief Operating Officer of the nonprofit Clean Climate Coalition, found herself leading the communication and implementation of a full company reorganization prompted by the voluntary departure of a senior leader. She had never led such an effort, no one else on the team had experience with such an initiative, and there was only a week to assemble the entire plan. Although she felt overwhelmed, she also viewed this as an opportunity to impact the organization’s culture and all its employees positively. Amy selected the Hussain et al. Model of Change (2018), which is an expansion of Lewin’s Three Phase Model of Change (Lewin, 1947), as a guide to lay out an achievable plan and timeline while being cognizant of organizational constraints.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Organizational change -- Case studies